2022
DOI: 10.1177/20436106221117573
|View full text |Cite
|
Sign up to set email alerts
|

Utterance chains: A dialogic route to speculative thinking-with toddlers in the Chthulucene

Abstract: Sustained shared thinking dialogues which focus on teacher talk with preschool learners have long been considered an important route to learning progression. Toddlers, however, seldom engage in dialogues through talk alone, and their encounters are often fleeting. As a consequence, they are often positioned on the periphery of learning dialogues that are granted primacy in the Capitalocene, because they must first acquire adult forms of communication and their meanings before thought becomes possible. Viewed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Similarly, Pandya and Mills (2019) found that elementary students employed carnivalesque humor to alleviate tension and challenge the seriousness of the situation. White (2022) explored toddlers' meaning making with Bakhtin's notion of utterances. The data found that toddlers coconstituted utterance chains through subtle, fleeting, and embodied language acts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Pandya and Mills (2019) found that elementary students employed carnivalesque humor to alleviate tension and challenge the seriousness of the situation. White (2022) explored toddlers' meaning making with Bakhtin's notion of utterances. The data found that toddlers coconstituted utterance chains through subtle, fleeting, and embodied language acts.…”
Section: Literature Reviewmentioning
confidence: 99%